Diverted total syntheses of potent cell adhesion inhibitor peribysin E analogues - Handore, Kishor L.; Reddy, D. Srinivasa (Organic Letters, 2013)
Preliminary results from a program aimed at the creation of a focused library of analogues around the natural product peribysin E, a potent biologically active and structurally fascinating molecule, are reported. The total synthesis of (+/-)-peribysin E was accomplished using a short route. Eight new analogues of the natural compound have been accomplished by means of ``diverted total synthesis'' in less than 10 steps. The present effort highlights protecting-group-free total syntheses and the shortest route to access these functionally embellished hydrindanes.

Diastereoselective synthesis of cyclic and spirocyclic quaternary carbons via iron-catalyzed ring contraction of cyclic ketones: a formal synthesis of perhydrohistrionicotoxin - Survase, Vijayanand U.; Rokade, Avinash D.; Handore, Kishor L. (Organic Letters, 2025)
The iron-catalyzed hydrogen atom transfer (HAT)-initiated Dowd-Beckwith rearrangement presents a new approach for synthesizing cyclic and spirocyclic quaternary carbons from readily available beta-keto esters and cyclic diketones with high yields. This reaction proceeds in a stereocontrolled manner, enabling the formation of synthetically valuable cyclic ketones with two contiguous stereocenters, including quaternary centers. This transformation introduces an innovative bond disconnection strategy for ring-contraction reactions. Additionally, a short formal synthesis of perhydrohistrionicotoxin was efficiently achieved using this methodology.